The Effect of Health Education about Puberty on Knowledge of Physical Changes in the Early Youth in MTS Al-Ikhwan, Tidore Island - Triany L Pelu; Halil, Na’mira (International Journal of Scientific Research and Management (IJSRM), 2022)
Physical changes are one of the physiological characteristics of early adolescents in entering puberty. Physical changes are often a problem for adolescents if the meaning of these changes leads to negative perceptions. These negative perceptions require the transfer of knowledge in order to provide an understanding of the physical changes that occur. One form of distribution of knowledge is through health education. The results of the 2012 Indonesian Youth Demographic and Health Survey (SDKI-R) in Aulia & Antika (2018) stated that as many as 13.3% of young women did not know anything about their physical changes during puberty. In fact, 47.9% of adolescent girls do not know the time of puberty. This lack of knowledge of adolescents results in a lack of knowledge of adolescents when experiencing a transition period. The transition period that occurs in adolescents is a vulnerable period for puberty adolescents, because adolescents experience rapid changes and involve physical changes including changes in body size, changes in body proportions and level of self-understanding, especially in terms of physical and sexual (Pasaribu, Ramayanti & Puri). , 2015). This study uses a quasi-experimental design based on a one group pre-post test design. The research sample is the entire population (total sampling), which is 45 students at MTs Al-Ikhwan Tidore Islands. Data analysis used the Wilcoxon test. The results showed that there was an effect of health education on puberty on knowledge of physical changes in early adolescents at MTs Al-Ikhwan Tidore Islands with p-value = 0.000. It was concluded that there was an effect of health education on puberty on knowledge of physical changes in early adolescence. This research still has many weaknesses, however, it is hoped that the results obtained can be used as material for other researchers to conduct further research on puberty with different designs and methods of health education.